TINGKAT KEPUASAN PENGGUNA LAYANAN MANGUPURA WOMAN SERVICES DI KABUPATEN BADUNG TAHUN 2016 - Dewi, Anak Agung Istri Ratna Maadnyani; Nopiyani, Ni Made Sri (ARCHIVE OF COMMUNITY HEALTH; Vol 4 No 1 (2017): Juni (2017), 2019)
A mobile early detection of breast cancer named ‘Mangupura Woman Services’ (MAWAS) has been conducted by Badung District Health office, Bali Province. Evaluation of users’ satisfaction towards MAWAS has not been conducted. This study aimed to measure users’ satisfaction levels towards MAWAS. A cross-sectional study was conducted in Badung to 90 respondent who recruited purposively based on the criteria of women in reproductive age who have utilized MAWAS. Users’ satisfaction was explored from five dimensions of healthcare quality including tangible, reliability, responsiveness, assurance and empathy. Data was analyzed using Importance Performance Analysis and Cartesius Diagram.  The highest importance score was in dimension of assurance (333,67) and the lowest was in responsiveness (323). The highest performance score was in dimension of empathy (310,25) and the lowest was in reliability (293,6). Empathy was the dimension with the highest level of satisfaction (94,66%) and reliability was the lowest (87,90%). Components of MAWAS that should be the main priorities for improvement were the comfort of service area, skill and ability of providers, information about service procedures and examination results. This study showed that tangible and reliability dimensions were perceived as unsatisfactory. Meanwhile, responsiveness, assurance and empathy dimensions were considered as satisfactory. Therefore, the managers of MAWAS should conduct training to improve the skill of service providers in providing quality services for the community. Keywords: User’s satisfaction, mobile screening, breast cancer, Badung